Observaciones en la nidificacion de Pachodynerus peruensis (Sauáure)(Hymenoptera: Vespidae: Eumeninae) - Chiappa, E.=700 1 Rojas, M.
(En, Es)
Ilus., 10 ref
Keywords: HYMENOPTERA; VESPIDAE; NIDIFICACION; COMPORTAMIENTO; BIOLOGIA; ESPECIES; CHILE; PACHODYNERUS PERUENSIS; REVISTA CHILENA DE ENTOMOLOGIA